Boosting oxygen reduction activity and enhancing stability through structural transformation of layered lithium manganese oxide - Xuepeng Zhong (Nature Portfolio, 2021)
Structural degradation in manganese oxides leads to unstable activity during long-term cycles. Herein, authors demonstrated that reduced unstable O 2p holes and the short interlayer distance of layered lithium manganese oxide are favorable for excellent electrocatalytic stability and activity.